Depression, anxiety, and prevalent diabetes in the Chinese population: findings from the China Kadoorie Biobank of 0.5 million people. - Mezuk, B; Chen, Y; Yu, C; Guo, Y; Bian, Z; Collins, R; Chen, J; Pang, Z; Wang, H; Peto, R; Que, X; Zhang, H; et al. (2013)
OBJECTIVE: Despite previous investigation, uncertainty remains about the nature of the associations of major depression (MD) with type 2 diabetes mellitus (T2DM), particularly in adult Chinese, and the relevance of generalized anxiety disorder (GAD) for T2DM. METHODS: Cross-sectional data from the China Kadoorie Biobank Study, a sample of approximately 500,000 adults from 10 geographically defined regions of China, were analyzed. Past year MD and GAD were assessed using the Composite International Diagnostic Inventory. T2DM was defined as either having self-reported physician diagnosis of diabetes at age 30 or later ("clinically-identified" cases) or having a non-fasting blood glucose≥11.1mmol/L or fasting blood glucose≥7.0mmol/L but no prior diagnosis of diabetes ("screen-detected" cases). Logistic regression was used to assess the relationship between MD and GAD with clinically-identified and screen-detected T2DM, adjusting for demographic characteristics and health behaviors. RESULTS: The prevalence of T2DM was 5.3% (3.2% clinically-identified and 2.1% screen-detected). MD was significantly associated with clinically-identified T2DM (odds ratio [OR]: 1.75, 95% confidence interval (CI): 1.47-2.08), but not with screen-detected T2DM (OR: 1.18, 95% CI: 0.92-1.51). GAD was associated with clinically-identified (OR: 2.14, 95% CI: 1.60-2.88) and modestly associated with screen-detected (OR: 1.44, 95% CI: 0.99-2.08) T2DM. The relationship between MD and GAD with T2DM was moderated by obesity. CONCLUSION: MD is associated with clinically-identified, but not screen-detected T2DM. GAD is associated with both clinically-identified and screen-detected T2DM. The relationship between MD and T2DM is strongest among those who are not obese.